1989
DOI: 10.1677/joe.0.1200531
|View full text |Cite
|
Sign up to set email alerts
|

Peptides related to α-melanocyte-stimulating hormone are commonly produced by human pituitary corticotroph adenomas: no relationship with pars intermedia origin

Abstract: The presence of immunoreactive (ir)-alpha-MSH has been investigated by immunocytochemistry in 24 pituitary adenomas and one case of corticotroph hyperplasia causing Cushing's disease, in four adenomas causing Nelson's syndrome, and in ten 'silent' corticotroph adenomas. It was found that a high proportion of these adenomas have a population of cells containing ir-alpha-MSH in addition to ir-ACTH. In some instances, these adenomas were clearly not associated with the residual intermediate lobe of the pituitary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…ACTH to IR p-END (p-LPH + p-END) molar ratios were 0.85 in the adenoma and 0.83 in the tissues indicated that the adenoma contained more than 25 times higher IR a-MSH than the surrounding tissues. The level in the adenoma (5.0 ng/mg wet weight) was similar to what was previously reported for corticotroph adenomas (5,200 ± 2, lOOng/g wet weight; mean ± SEM) [5], Concentrations of the other anterior pituitary hormones in the surrounding tissues (expressed as per milligram wet weight) were 930 ng for GH. 360 ng for PRL.…”
Section: Immunoreactivity O F Pomc-derived Peptides In the Adenoma Ansupporting
confidence: 88%
See 1 more Smart Citation
“…ACTH to IR p-END (p-LPH + p-END) molar ratios were 0.85 in the adenoma and 0.83 in the tissues indicated that the adenoma contained more than 25 times higher IR a-MSH than the surrounding tissues. The level in the adenoma (5.0 ng/mg wet weight) was similar to what was previously reported for corticotroph adenomas (5,200 ± 2, lOOng/g wet weight; mean ± SEM) [5], Concentrations of the other anterior pituitary hormones in the surrounding tissues (expressed as per milligram wet weight) were 930 ng for GH. 360 ng for PRL.…”
Section: Immunoreactivity O F Pomc-derived Peptides In the Adenoma Ansupporting
confidence: 88%
“…Indeed, accumu lating morphological [5. 19-22] and biochemical [5,23] studies have proposed that the Lamberts' hypothesis should not be accepted or. at least, should be revised.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this latter possibility data have been presented suggesting that adrenocorticotrophic hormone-secreting pitu¬ itary adenomas may originate from either the anterior lobe or intermediate-lobe remnants (Lamberts, De Lange & Stefanko, 1982;Lamberts, 1987). The 'intermediate-lobe hypothesis' has been criticized on the basis of clinical studies (Koppeschaar, Croughs, Thijssen & Schwarz, 1986;Pieters, Smals, Goverde et al 1982) and morphological observations (McNicol, Teasdale & Beastall, 1986;Coates, Doniach, Hale & Rees, 1986;Coates, Doniach, Wells et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells containing a.-MSH of the pars distalis have been previously described in humans and dogs with Cushing's disease (3,6,8,9,11). In the rat pituitary tumor, however, cells containing a-MSH have not been verified so far.…”
mentioning
confidence: 98%
“…Submissions will be reviewed for clarity and relevance to the journal readership. Comments (3,6,8,9,11 For immunohistochemical detection of a-MSH, prolactin (PRL), and proliferating cell nuclear antigen (PCNA), selected tissue sections were processed by a labeled streptavidin-biotin (LSAB) method. In brief, the paraffin section was deparaffinized, treated sequentially with rabbit anti-a-MSH antibody (1:500, Biogenesis, Inc, NH), rabbit anti-rat prolactin antibody (1:1,000, Chemicon International Co, Ltd, CA), or mouse anti-PCNA antibody (1:100, DAKO Japan Co., Ltd., Tokyo, Japan) as the primary antibody, followed by staining with an LSAB kit (DAKO Japan Co, Ltd …”
mentioning
confidence: 99%